1998
DOI: 10.1152/jn.1998.79.4.2231
|View full text |Cite
|
Sign up to set email alerts
|

Painful Stimuli Evoke Potentials Recorded Over the Human Anterior Cingulate Gyrus

Abstract: Clinical studies of cingulotomy patients and imaging studies predict that the human cingulate gyrus might display pain-related activity. We now report potentials evoked by painful cutaneous stimulation with a CO2 laser (LEP) and recorded from subdural electrodes over the medial wall of the hemisphere. In response to facial laser stimulation on both sides, a negative (latency 211-242 ms) and then a positive wave (325-352 ms) were recorded from the cortex of right medial wall and from the falcine dura overlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
85
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(100 citation statements)
references
References 22 publications
13
85
1
1
Order By: Relevance
“…Whereas Lenz et al (1998) and Rios et al (1999) reported only "late" cingulate responses at 220 -250 ms, Ohara et al (2004a,b) recorded more recently a negative wave at 140 -160 ms, i.e., at latencies close to those obtained in our patients. The peak latencies of opercular and CC responses were almost identical in one patient and delayed by 10 -15 ms in two.…”
Section: Response Localizationsupporting
confidence: 74%
See 1 more Smart Citation
“…Whereas Lenz et al (1998) and Rios et al (1999) reported only "late" cingulate responses at 220 -250 ms, Ohara et al (2004a,b) recorded more recently a negative wave at 140 -160 ms, i.e., at latencies close to those obtained in our patients. The peak latencies of opercular and CC responses were almost identical in one patient and delayed by 10 -15 ms in two.…”
Section: Response Localizationsupporting
confidence: 74%
“…However, emotional and vegetative reactions involving the rostral-perigenual CC are not likely to be triggered by our laser stimulus, which produces a sharp pinprick sensation qualified as "painful," but seldom perceived as strongly unpleasant or hyperalgesic. In accordance with this view, Lenz et al (1998) using laser stimulation and subdural electrodes recorded local maxima of CC LEPs 30 mm anterior to the central sulcus, i.e., over the MCC, and not in regions rostral or caudal to this area.…”
Section: Discussionsupporting
confidence: 57%
“…The lack of perceived intensity difference may be because the brevity of each stimulus did not provide the temporal summation necessary for accurate intensity estimation (Torebjork et al, 1984;Magerl et al, 1999); in addition, the short intervals between the CS and TS may have impaired the ability of our subjects to discriminate clearly between them and to evaluate intensity differences easily. Finally, the evoked potentials we recorded at Cz are probably generated within or near the anterior cingulate gyrus (Lenz et al, 1998) and their amplitudes may not be specifically and exclusively related to perceived stimulus intensity. …”
mentioning
confidence: 87%
“…Since pain evoked-potential studies suggest short-latency activation in dPCC (Lenz et al, 1998;Bentley et al, 2003;Schlereth et al, 2003) and there is a low level of emotionrelevant activation here (Vogt et al, 2003;Vogt, 2005), nociceptive activity in pMCC and dPCC is not likely affective. Since the rabbit and rat do not have a dPCC, dorsal RSC may perform similar functions in these species.…”
Section: Nociception Extends Beyond Anterior Cingulate Cortexmentioning
confidence: 99%